2015
DOI: 10.1080/23268743.2015.1052937
|View full text |Cite
|
Sign up to set email alerts
|

Male gays in the female gaze: women who watch m/m pornography

Abstract: Male gays in the female gaze: Women who watch m/m pornographyThis paper draws on a piece of wide-scale mixed-methods research that examines the motivations behind women who watch gay male pornography. To date, there has been very little interdisciplinary research investigating this phenomenon, despite a recent survey by PornHub (one of the largest online porn sites in the world) showing that gay male porn is the second most popular choice for women porn users out of 25+ possible genre choices (PornHub, 2014). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 28 publications
4
65
0
4
Order By: Relevance
“…While much of the previous literature has focused on demarcations that set apart women’s from men’s consumption, we find that women use pornography in a fairly similar way to men as reported in recent studies (McCormack and Wignall, 2017). Prior research suggests that women are able to identify more with the erotic narratives in erotica (Chowkhani, 2016; Hardy, 2009; Wilson-Kovacs, 2009) or other alternative porn categories (Neville, 2015, 2018), and therefore tend to prefer them. Our study, however, shows that women also find pleasure in mainstream pornography, including hardcore categories, even though they do not always identify with the actors and stories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much of the previous literature has focused on demarcations that set apart women’s from men’s consumption, we find that women use pornography in a fairly similar way to men as reported in recent studies (McCormack and Wignall, 2017). Prior research suggests that women are able to identify more with the erotic narratives in erotica (Chowkhani, 2016; Hardy, 2009; Wilson-Kovacs, 2009) or other alternative porn categories (Neville, 2015, 2018), and therefore tend to prefer them. Our study, however, shows that women also find pleasure in mainstream pornography, including hardcore categories, even though they do not always identify with the actors and stories.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of empirical research focusing on women could be attributed to pornography being usually considered as beyond their reach and interest. Neville (2015) argues that this is due to social expectations warranting women to refrain from public displays of their sexuality and pornography’s openness to the depiction of sex. For example, Wilson-Kovacs (2009: 156) suggests that discussing porn preferences is a taboo topic for women, and as such, ‘pornography is simply what the male partner invariably chooses’.…”
Section: Pornography Consumption and Sexualitymentioning
confidence: 99%
“…The article argues that, based on the findings of the study, women not only have a positive response to gay porn and the gay sex represented but also report feelings of empathy. Ramsay's article acts as a contribution to an emergent literature on the diverse audiences for gay porn that includes Lucy Neville's (2015) excellent essay also on female consumption of gay porn, Florian Voros' (2015) equally fascinating analysis of male porn viewers and the major audience research project conducted by Clarissa Smith, Feona Attwood, and Martin Barker (2011), and which all work collectively to explode stereotypes and generalizations about porn audiences, who they are and how they relate to porn materials.…”
Section: John Mercermentioning
confidence: 99%
“…However, not many publications have specifically addressed the media through the prism of queer theory and psychoanalysis. An exception seems to be the evolving field of porn studies, which has shown a tendency to take psychoanalytic concepts into account, as various articles in the recently launched journal of the same title attest (Neville, 2015;Ryberg, 2015;Varghese, 2016).…”
Section: Queer Theory and Intersectional Studiesmentioning
confidence: 99%